Clima familiar y desarrollo de habilidades blandas de estudiantes de la Escuela de Ciencias de la Comunicación, Universidad Nacional de Trujillo, 2021 - Marquina Gonzales, Claudia Stephany (2023)
The present investigation was carried out with the purpose of analyzing how the family climate influences the development of soft skills of the students from the Professional School of Communication Sciences of the National University of Trujillo 2021, in which a sample of 40 students were taken, considering the total population. For the development of this research, the inductive - deductive, analytical - synthetic method, and statistical method were used, in addition, the interview and survey technique was used, in turn, instruments such as the questionnaire and the interview guide. According to the information obtained in this research, it can be said that the family climate negatively influences the development of soft skills of Communication Sciences students, from the communication between its members, the interpersonal relationship, the motivation and the environment that can develop. This is reflected when they carry out teamwork and the organization of assigned tasks, in addition as Pelegrina, Linares, Casanova, (2001) points out: "a favorable family environment, marked by commitment, affects an adequate academic performance, as well as a democratic family coexistence between parents and children, in addition, the behaviors of parents mediate in the academic results of the students. A family environment that stimulates pleasure for academic tasks, curiosity for knowledge, persistence towards academic achievement is related to good academic results.